Irrigation in farmers' land-use choices: Panel-data evidence from Viet Nam - Quang Thanh Ngo; Khai Duc Luu; Phuc Ngoc Doan; Hoa Thi Hoang Nguyen; Lai Thi Cam Phan; Phuoc Huu Vo; Thi Viet Thuy Ha; Danh Ngoc Nguyen (Cogent Economics & Finance, 2022)
Irrigation and land use are crucial issues in rural sustainable development. The current study modifies the sustainable framework of livelihoods to clarify the role of irrigation management in farmers' land-use choices. A five-wave panel dataset of 1,534 farms for the period 2008-2016 in Viet Nam (with a total of 7,669 observations) is used for analyzing the influence of irrigation management on land-use selections, employing a fixed-effects model. Irrigation management is investigated in six aspects: (i) the physical conditions, (ii) the ownership of facilities, (iii) the operations, (iv) the management responsibility shift, (v) the decision-making, and (vi) the maintenance. The results reveal that the overall effects of irrigation management are so different, depending on the types of land uses. On top of that, different aspects of irrigation management have diversified influences on types of land uses. The findings lead to several important implications related to irrigation management that are relevant to farmers and policymakers. Different stakeholders, organizations/institutions, and farming households play differently effective roles in irrigation management. In general, policies can be conducted through the development of a lined irrigation network, and decision-making in operations of irrigation, maintenance of irrigation, and irrigation maintenance should give more power to farmers' groups.
Keywords: Q12; Q15; Q24; C33; 330; Irrigation; Land use decision making; panel data; fixed-effects model; Vietnam